2019
DOI: 10.3390/su11226428
|View full text |Cite
|
Sign up to set email alerts
|

Inventory Sharing Strategy for Disposable Medical Items between Two Hospitals

Abstract: When urgent situations occur (e.g., inaccurate demand forecast, traffic accidents, or infectious disease outbreaks), the stock of rescue medical items in the hospital might not be enough to cater to the drastically increased demand. Comparing with placing an expensive emergent replenishment order with dealers, requesting inventory sharing from another hospital with excessive stocks could save time and cost. This paper investigates the operation of the inventory sharing mechanism between two independent hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…For instance, the inventory at the automotive factory during a demand decrease can be redirected to the electronics and medical factories to avoid shortages. This observation is in line with literature arguing that sharing inventories can be profitable (Zhang et al, 2019) and allow better matching of supply and demand (Villa & Castañeda, 2018). Somarin et al (2023) affirmed that stock reallocation ensures the availability of materials and avoids backorder situations.…”
Section: Discussion and Managerial Insightssupporting
confidence: 85%
“…For instance, the inventory at the automotive factory during a demand decrease can be redirected to the electronics and medical factories to avoid shortages. This observation is in line with literature arguing that sharing inventories can be profitable (Zhang et al, 2019) and allow better matching of supply and demand (Villa & Castañeda, 2018). Somarin et al (2023) affirmed that stock reallocation ensures the availability of materials and avoids backorder situations.…”
Section: Discussion and Managerial Insightssupporting
confidence: 85%
“…The results illustrated that the sharing mechanisms helped improve the freshness ratio and reduced expiry in a medical inventory system (Jin and Agirbas, 2013), resulting in a wastage mitigation rate, total stock depletion and thus a decrease in the stock depletion period (den Nijs et al, 2022;Sohrabi et al, 2021). Furthermore, it helped reduce the risk of shortage and overall inventory levels while increasing the overall resource utilisation rate (Mehrotra et al, 2020;Zhang et al, 2019). The studies also illustrated that under the sharing mechanism, inventory holding and stockout costs and the system's operational costs, were reduced and ultimately gained an extra profit (Chiu et al, 2019;Jin and Agirbas, 2013;Oeser and Romano, 2021).…”
Section: Healthcare Supply Chains: Inventory-sharing Configurationsmentioning
confidence: 94%
“…The results found that the shortage and cost aspects benefited the most from the adoption of LT policies (Figure 11), which significantly improved service levels (AlAzmi and AlRashidi, 2019; Postacchini et al, 2016;Wu and Mao, 2017) and mitigated the risk of a drug shortage as well as inventory levels (Parvin et al, 2018;Zhang et al, 2019). In addition, this collaboration could improve the product utilisation rate (Zhang et al, 2022), decreasing wastage (Jin and Agirbas, 2013).…”
Section: Healthcare Supply Chains: Inventory-sharing Configurationsmentioning
confidence: 97%
See 2 more Smart Citations